Ein Diener seiner Herren Werdegang des österreichischen Geheimagenten Gustav Zerffi (1820-1892) - Frank, Tibor (2002)
The biography of Gustavus G. Zertfi (1820-1892) is the first analytical introduction to the Habsburg secret service in the 1850s and 1860s through the case study of a secret agent. By strange coincidence, it is also a major contribution to the. beginnings. of modem Japanese historiography as Zerffi's The Science of History provided the first basic text for Japanese scholars on modem European history and historians after the Meiji revolution of 1868. Though. probably the most formidable. secret agent in the ."neo-absolutistic" Habsburg Empire of the mid-19th century, G. G. Zerffi was an obscure and relatively little known figure in his own time. Over a period. of close to 16. years, Zerffi sent some 2,000 numbered intelligent reports to the Habsburg government in Vienna from Serbia, the Ottoman Empire, Paris, and, mainly, from London (1849-1865). The. biography serves as an introduction to all the available secret reports by Zerffi collected from Austrian and, to a smaller extent, Russian archives, publishing them in the Get-man original as an appendix of his work. Through the life and activities. of one particular figure the book opens up. several chapters of 19th century Europe, Britain, and Japan and contributes significantly to the understanding of the revolutions of 1848-1849 and. their dreadful suppression in the whole continent of Europe. It provides particularly new insight in the working and methods of authoritarian, "pre-dictatorial" Central and East. European secret police systems, censorship, and thought control. All over Europe the police preferred to use highly qualified agents. with, the knowledge of several languages, as well as the history and culture of many regions in order to collect reliable and. varied information. This. in turn was used by the governments to maintain their control over practically the whole of the European continent in much of the 1850s and 1860s.. Several of these well paid police. agents were. prominent professionals such as G. G. Zerffi who came to be one of the founders and first chairmen of the Royal Historical Society in London. It was in this capacity that he contributed to the humanities in Britain as well as to the rise of modem Japanese historiography. This is the first book to provide a thorough introduction to G. G. Zerffi's basically unknown British scholarship from the late 1860s through the early 1890s. A relevant and topical contribution to the understanding of the nature and making of Central and East European autocracies in the mid-19th century, the book will also help the reader to assess the prehistory and early development of modem dictatorial systems in the region. Most of the book is based on primary sources scattered all over Europe in dozens of archives in Vienna, Budapest, London, Moscow, Amsterdam, and Bonn.